PENERAPAN RESTORATIVE JUSTICE OLEH KEPOLISIAN NEGARA REPUBLIK INDONESIA UNTUK MEWUJUDKAN TUJUAN HUKUM - Armunanto Hutahaean (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Nowadays, settlement of criminal cases out of the court through restorative justice is essential for Indonesian society. State Police of the Republic of Indonesia as the bearer of the state government's function of law enforcement duties, in addition to provide protection, safeguard and service to public are expected to be able to realize the demands of the community to achieve justice. The public has high expectations for the State Police of the Republic of Indonesia as one of the law enforcement officers, who are authorized by law as investigators to carry out investigations of all criminal acts in the context of law enforcement. Certainly, law enforcement is carried out according to the priority program of the National Police Chief which carries the concept of Transformation towards a Predictive, Responsive and Just Transparency Police (PRESISI) for the realization of legal purpose.